2015
DOI: 10.1096/fj.15-275396
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid 2‐mediated shear‐stress responses in C2C12 myoblasts are regulated by serum and extracellular matrix

Abstract: The developmental sensitivity of skeletal muscle to mechanical forces is unparalleled in other tissues. Calcium entry via reputedly mechanosensitive transient receptor potential (TRP) channel classes has been shown to play an essential role in both the early proliferative stage and subsequent differentiation of skeletal muscle myoblasts, particularly TRP canonical (TRPC) 1 and TRP vanilloid (TRPV) 2. Here we show that C2C12 murine myoblasts respond to fluid flow-induced shear stress with increments in cytosoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 89 publications
(212 reference statements)
0
27
0
Order By: Relevance
“…Although Boonen et al and Kook et al have not reported any positive effect of cyclic stretching, passive tension seems to be a minimum requirement to promote maturation of muscle cells. Mechanical stimulation of skeletal muscle cells through fluid generated shear stress has been reported in some cases to promote the differentiation process (192)(193)(194). High shear stress (5-10 Pa) has been shown to be detrimental to cells, however the effect of lower shear stress ranges (1-1,400 mPa) have been investigated and found to positively influence mechano-transduction in muscle cells.…”
Section: Is a One-step Proliferation/ Differentiation Bioprocess Feasmentioning
confidence: 99%
“…Although Boonen et al and Kook et al have not reported any positive effect of cyclic stretching, passive tension seems to be a minimum requirement to promote maturation of muscle cells. Mechanical stimulation of skeletal muscle cells through fluid generated shear stress has been reported in some cases to promote the differentiation process (192)(193)(194). High shear stress (5-10 Pa) has been shown to be detrimental to cells, however the effect of lower shear stress ranges (1-1,400 mPa) have been investigated and found to positively influence mechano-transduction in muscle cells.…”
Section: Is a One-step Proliferation/ Differentiation Bioprocess Feasmentioning
confidence: 99%
“…The most well-known muscular genetic disease, Duchenne muscular dystrophy (DMD), results from mutations in the dystrophin gene affecting the transmission of contraction from the sarcomeres to the ECM [3]. Miniaturized models of DMD have been described, including either in vitro models of diseased muscle [17,41] or microfluidic platforms for the investigation of pathological mechanisms at a cellular level [14,18]. A study by Serena and coworkers [17] was based on microgrooved soft polymeric substrates coated with laminin or fibronectin (Figure 3Ai).…”
Section: Miniaturized Models For Skeletal Muscle Diseasesmentioning
confidence: 99%
“…Primary human myoblasts were cultured on laminin, fibronectin or collagen type I substrates in the presence of a FGF- gradient, highlighting how differences in ECM can modulate myoblasts chemotaxis and, thus, their recruitment to the injury site, hindering the physiological healing process of the muscle. Dysregulation of mechanosensitive ion channels also has a key role in the pathological mechanism of DMD [42] and, recently, a 2D microfluidic device was described that enabled the characterization of myoblast mechanotransduction operated by ionic channels subjected to interstitial stress [14]. C2C12 were cultured in a microfluidic chip coated with laminin or fibronectin and subjected to flow.…”
Section: Miniaturized Models For Skeletal Muscle Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the presence of TRPC1(Louis et al, 2008), TRPM7 and TRPV2(Kurth et al, 2015) 347 channel activity was shown in skeletal muscle myoblasts, with these channels controlling 348 processes such as cell migration or cellular fusion(Louis et al, 2008;Antigny et al, 2017).349Of note, TRP channels have been shown to mediate CCE in different systems(Mignen et 350 al., 2017). To determine the molecular player(s) potentially involved in C2C12 light-driven 351 calcium entry, we used RT-PCR to detect the possible expression of different TRP channels 352 in these cells.…”
mentioning
confidence: 99%